Flexible Power and Biomass-To-Methanol Plants With Different Gasification Technologies - A. Poluzzi; G. Guandalini; S. Guffanti; M. Martinelli; S. Moioli; P. Huttenhuis; G. Rexwinkel; J. Palonen; E. Martelli; G. Groppi; M. C. Romano (Frontiers in Energy Research, 2022)
The competitiveness of biofuels may be increased by integrating biomass gasification plants with electrolysis units, which generate hydrogen to be combined with carbon-rich syngas. This option allows increasing the yield of the final product by retaining a higher amount of biogenic carbon and improving the resilience of the energy sector by favoring electric grid services and sector coupling. This article illustrates a techno-economic comparative analysis of three flexible power and biomass to methanol plants based on different gasification technologies: direct gasification, indirect gasification, and sorption-enhanced gasification. The design and operational criteria of each plant are conceived to operate both without green hydrogen addition (baseline mode) and with hydrogen addition (enhanced mode), following an intermittent use of the electrolysis system, which is turned on when the electricity price allows an economically viable hydrogen production. The methanol production plants include a gasification section, syngas cleaning, conditioning and compression section, methanol synthesis and purification, and heat recovery steam cycle to be flexibly operated. Due to the high oxygen demand in the gasifier, the direct gasification-based plant obtains a great advantage to be operated between a minimum load to satisfy the oxygen demand at high electricity prices and a maximum load to maximize methanol production at low electricity prices. This allows avoiding large oxygen storages with significant benefits for Capex and safety issues. The analysis reports specific fixed-capital investments between 1823 and 2048 €/kW of methanol output in the enhanced operation and LCOFs between 29.7 and 31.7 €/GJLHV. Economic advantages may be derived from a decrease in the electrolysis capital investment, especially for the direct gasification-based plants, which employ the greatest sized electrolyzer. Methanol breakeven selling prices range between 545 and 582 €/t with the 2019 reference Denmark electricity price curve and between 484 and 535 €/t with an assumed modified electricity price curve of a future energy mix with increased penetration of intermittent renewables.